The road to specialization in agricultural production: Evidence from rural China - Qin, Yu; Zhang, Xiaobo (International Food Policy Research Institute, 2012)
Because many rural poor live in areas far away from markets, we investigate whether better road access could help improve their livelihood and reduce rural poverty. We use three waves of a primary panel survey at the household level conducted in 18 remote natural villages in China to study how road access shapes farmers’ agricultural production patterns and input uses and affects rural poverty. Our results show that access to roads is strongly associated with specialization in agricultural production. In natural villages with better road access, farmers plant fewer numbers of crops, purchase more fertilizer, and invest more money in labor. In combination with such factors, road connections improve household agricultural income—in particular, cash income—and contribute to poverty reduction in the surveyed villages. However, better access to rural roads does not appear to bring about significant changes in nonagricultural income.